Konformitas Standar Indeks Siaran Televisi: Tantangan Komisi Penyiaran Indonesia (KPI) dalam Psikologi Komunikasi Audiens di Era Postmodernisme - Razali, Geofakta (Magister of Communication Science, Sahid University Jakarta., 2024)
This study aims to evaluate the relevance and effectiveness of the Indonesian Broadcasting Commission (KPI) in regulating television broadcasts in the postmodern era. By analyzing the 2024 Period 2 Television Broadcast Quality Index (IKPSTV) results, the study explores four key aspects: broadcast quality standards, media literacy among audiences, the use of digital technologies, and the integration of postmodernist values into new media regulation. The findings reveal gaps between KPI standards and the increasingly diverse needs of audiences. Low media literacy and traditional regulatory approaches are identified as major challenges. To enhance KPI's relevance, the study recommends employing digital technologies such as big data and artificial intelligence (AI), promoting media literacy campaigns, and adopting a hybrid regulatory approach inclusive of postmodernist values. These findings provide strategic insights to improve KPI's effectiveness in overseeing both traditional and digital media.Keywords: KPI, postmodernism, media literacy, digital technology, media regulation, audience communication.